ANALISA PENGARUH MOTIVASI KERJA, KOMITMEN, DAN KEMAMPUAN KERJA TERHADAP KINERJA GURU SMK PELITA NUSANTARA 1 SEMARANG - Susanti Wahyuningsih (STIE Pelita Nusantara Semarang, 2015)
Declining student achievement happens in SMK Pelita Nusantara 1 Semarang estimated as maximal performance of teachers in guiding students. The ability of teachers views of education and training is still less than the maximum because of the lack of opportunity to follow pendididikan and training. Census method used in this study. The fourth hypothesis proposed in this study are all accepted. Results of research by multiple linear regression analysis showed that the most dominant variable is the motivation to work with the highest regression coefficient, amounting to 0.433 followed by a variable commitment, amounting to 0.281; and variable working capability of 0,260. The coefficient of determination (R2) of 0.577, or (57.7%), describes the work motivation, commitment and ability to work simultaneously affect the performance of teachers. While the rest (100% - 57.7% = 42.3%) is explained by other variables outside of the variables studied.